Review of Hydrometra gracilenta Horváth, 1899 (Hemiptera: Heteroptera: Hydrometridae) in Italy, with notes on its general distribution - Cianferoni, Fabio; Dell’olmo, Lorella; Lastrucci, Lorenzo (Zootaxa, 2015)
An annotated review of the known Italian distribution of Hydrometra gracilenta Horváth, 1899 is provided, plus unpublished data including a new record which increases the previously known range of the species in Italy. An updated map shows the currently known distribution of the taxon in Italy. An overlooked nomenclatural change is discussed, and the date of description for the genus Hydrometra Lateille is corrected from 1796 to 1797. The presence of H. gracilenta is excluded from Egypt, Sudan, and Rwanda.